A COGNITIVE STYLISTIC ANALYSIS OF PINK FLOYD’S SONG LYRIC “TIME” - Sirait, Anjeli Lorena; Siburian, Jessica Br.; Sitompul, Ines Margaretha; Rangkuti, Rahmadsyah (Ma Chung Press, 2024)
The objective of this paper is to describe how the content of song lyrics interacts with concepts of time, memory, and human experience and knowing how language and cognition are interrelated to create profound artistic expression in music through scheme theory, metaphor theory, and figures of speech as features of creativity and novelty in language use. The data was derived from the song entitled Time by Pink Floyd. The research method used in this study is qualitative descriptive. The result of this study is skillfully employing various figures of speech, such as metaphor, personification, and paradox, to convey the complexities of time, aging, regret, and the human experience. These literary devices engage the listener's intellect and emotions, prompting reflection on the passage of time and its impact on our lives. Furthermore, the song employs schema theory to activate the